Tobacco industry messaging around harm: Narrative framing in PMI and BAT press releases and annual reports 2011 to 2021 - Fitzpatrick, Iona; Dance, Sarah; Silver, Karin; Violini, Marzia; Hird, Thomas R. (Frontiers in Public Health, 2022)
Influencing public perception is a key way in which all transnational corporations (TNCs) maintain market dominance and political power. Transnational tobacco companies (TTCs) have a long history of leveraging narratives to serve commercial ambitions. The global reach of these companies’ narratives has been highlighted as a challenge in combatting public health problems caused by tobacco. The corporate power of TTCs is carefully curated, and their narratives play an important role in the setting of governance dynamics at local, national and transnational levels. This qualitative work explores and compares the language used by British American Tobacco (BAT) and Philip Morris International (PMI) around harm, harm reduction and terms used to refer to newer nicotine and tobacco products, including electronic cigarettes and heated tobacco products. We systematically examine framings used by these two TTCs through company reports published between 2011 and 2021. Qualitative coding was carried out by four coders, according to a protocol developed specifically for this work. We firstly identified the presence of pre-selected keywords and then assigned chunks of text containing those key words to one or more associated frames drawn from Boydstun’s policy frames codebook (2013). Qualitative coding identified the most common frames from Boydstun’s codebook and thematic analysis highlighted three overarching themes. The most common frames assigned were “capacity and resources”, “health and safety” and “economic” frames. The overarching themes were individualisation, normalisation, and regulation. These themes capture how both BAT and PMI use particular framings to downplay the role of TTCs in the perpetuation of population- and individual-level harms related to tobacco use. They seek to normalize their role in public discussions of health policy, to cast themselves as instrumental in the redress of tobacco-related inequalities and shift responsibility for the continuation of tobacco-product use onto individual consumers. These tactics are problematic for the effective and impartial development and implementation of local, national and international tobacco control agendas.